2018
DOI: 10.1590/1678-4162-9373
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of climate variables on Apis mellifera pollen foraging performance

Abstract: Pollination services performed by bees are essential for the reproduction of a great part of flowering plants. The pollen collected by Apis mellifera while performing pollination (bee pollen), has been incorporated into the human diet for its favorable nutritional components. Around 1,500 tons of bee pollen are produced annually worldwide, especially in Spain, China, Australia, Argentina, and Brazil. Despite the importance of bee pollen within apiculture, little is known about the effects of climate variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown that bee pollen has antioxidant, anti-inflammatory, anticarcinogenic, antibacterial and antifungal actions which provide health benefits to its consumer (Pascoal et al, 2014;Denisow & Denisow-Pietrzyk, 2016). However, the components in the pollen vary according to the pollen that the bees collect; it reflects its botanical origin, which, in turn, depends on the climatic conditions, soil type and time of year in which it was collected (Domínguez-Valhondo et al, 2011;Arruda et al, 2013;Ares et al, 2018;Mattos et al, 2018). In addition, commercial bee pollen undergoes a dehydration process to improve its conservation during storage, which also affects its characteristics (Domínguez-Valhondo et al, 2011;De-Melo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that bee pollen has antioxidant, anti-inflammatory, anticarcinogenic, antibacterial and antifungal actions which provide health benefits to its consumer (Pascoal et al, 2014;Denisow & Denisow-Pietrzyk, 2016). However, the components in the pollen vary according to the pollen that the bees collect; it reflects its botanical origin, which, in turn, depends on the climatic conditions, soil type and time of year in which it was collected (Domínguez-Valhondo et al, 2011;Arruda et al, 2013;Ares et al, 2018;Mattos et al, 2018). In addition, commercial bee pollen undergoes a dehydration process to improve its conservation during storage, which also affects its characteristics (Domínguez-Valhondo et al, 2011;De-Melo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These results differ from those obtained by Akhtar et al (2018) in Pakistan, who observed a negative correlation with relative humidity. On the other hand, de Mattos et al (2018) found positive correlations between relative humidity and the number of foraging A. mellifera in a tropical region in Brazil, mainly in autumn and winter.…”
Section: Discussionmentioning
confidence: 97%
“…Crop systems that have different sowing dates and exploit different canola genotypes can significantly influence the population abundance and seasonality of honeybees. This may be due to the indirect effects of the sowing date in conjunction with abiotic variables, such as air temperature, relative humidity, and precipitation, which may favour some species over others (de Mattos et al 2018; Soares et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, high humidity leads to a dilution of nectar and a disruption of the physical properties of pollen (Alves et al, 2015; Silva et al, 2013) which resulted in less attractiveness of the honey bees to the flower rewards. Periods of rainfall in addition to be positively correlated with relative humidity, make foraging activities almost impossible (De Mattos et al, 2018). Wet periods are linked with periods of low pollen foraging (Schneider & McNally, 1992).…”
Section: Discussionmentioning
confidence: 99%